Roles of Traditional, Online-Specific, and Cross-Channel Marketing Instruments in Multi- and Omnichannel Fashion Retail Brand Equity - Angelina Klink; Bernhard Swoboda (Journal of Consumer Behaviour, 2025)
Multi- and omnichannel retailers use various marketing instruments to position themselves as strong brands. However, we know surprisingly little about how strongly retail brand equity (RBE) benefits from the traditional, online-specific, or cross-channel instruments that consumers perceive when switching channels. This study fills this gap by leveraging categorization theory. It contributes to the literature by analyzing the roles of important marketing instruments for consumer loyalty decisions through offline and online RBE via a sample of 379 consumers surveyed at three different points in time as well as sequential mediation and cross-lagged structural equation modeling. The findings highlight the distinct importance of the indirect and total effects of the instruments for loyalty through offline and online RBE. Furthermore, offline and online RBE reciprocally affect loyalty decisions to different extents, providing additional insights into the roles of the instruments. These findings have direct implications for managers seeking to understand the role of marketing instruments and the interactive role of offline and online RBE in customer loyalty.
Keywords: 320; categorization theory; longitudinal modeling; offline and online retail brand equity; reciprocity